Sleep duration and body mass index and waist circumference among Us adults. (15th October 2013) - Ford, Earl S.; Li, Chaoyang; Wheaton, Anne G.; Chapman, Daniel P.; Perry, Geraldine S.; Croft, Janet B.
<x xml:space="preserve">Abstract</x> Objective To examine the form of the relationship between sleep duration and anthropometric measures and possible differences in these relationships by gender and race or ethnicity. Design and Methods Data for 13, 742 participants aged ≥20 years from the National Health and Nutrition Examination Survey 2005‐2010 were used. Sleep duration was categorized as ≤6 (short sleepers), 7‐9, and ≥10 hours (long sleepers). Results Short sleepers were as much as 1.7 kg/m2 (SE 0.4) heavier and had 3.4 cm (SE 1.0) more girth than long sleepers. Among participants without depression or a diagnosed sleep disorder, sleep duration was significantly associated with body mass index (BMI) and waist circumference in an inverse linear association in the entire sample, men, women, whites, African Americans, and participants aged 20‐39 years. No evidence for statistical interaction by gender and race or ethnicity was observed. Regression coefficients were notably stronger among adults aged 20‐39 years. Compared to participants who reported sleeping 7‐9 hours per night, short sleepers were more likely to be obese and have abdominal obesity. Conclusions In this nationally representative sample of US adults, an inverse linear association most consistently characterized the association between sleep duration and BMI and waist circumference.